Comparison Comparison of the Effectiveness of Manual and Machine Spray Equipment in Applying Bernouli's Principle: A T-shirt Study Among Cikole Farmers: Comparison of the Efficiency of Manual and Machine Sprayers in Agricultural Applications - Apryandi, Feri; Pratama, Aulia Shinta; Nisa, Najwa Khairun; Hidayanti, Refy; Azizah, Reva Nur (Jurnal Pendidikan Fisika dan Sains (JPFS), 2024)
This research compares the effectiveness of manual and machine sprayers in spraying applications on agricultural land. Research results show that machine sprayers, such as electric knapsack sprayers, are superior to manual sprayers in several aspects. The use of a machine sprayer increases work efficiency with more even fluid distribution, reduces operator fatigue, and allows area coverage of up to 1-2 hectares per hour. The average time needed to spray one hectare of land using a machine sprayer is around 30-45 minutes. In addition, the use of machine sprayers can optimize the use of chemicals by reducing waste due to uneven spraying by up to 20-30%. In terms of long-term operational costs, even though machine sprayers require a larger initial investment (around 20- 40% higher than manual sprayers), the resulting efficiency can reduce overall costs by 15-25%.